Safety, Quality, and Acceptability of Contraceptive Implant Provision by Community Health Extension Workers versus Nurses and Midwives in Two States in Nigeria. Issue 3 (23rd July 2021) - Douthwaite, Megan; Alabi, Olalere; Odogwu, Kingsley; Reiss, Kate; Taiwo, Anne; Ubah, Ebere; Uko‐Udoh, Anthony; Afolabi, Kayode; Church, Kathryn; Fenty, Justin; Munroe, Erik
Abstract: Task sharing is a strategy with potential to increase access to effective modern contraceptive methods. This study examines whether community health extension workers (CHEWs) can insert contraceptive implants to the same safety and quality standards as nurse/midwives. We analyze data from 7, 691 clients of CHEWs and nurse/midwives who participated in a noninferiority study conducted in Kaduna and Ondo States, Nigeria. Adverse events (AEs) following implant insertions were compared. On the day of insertion AEs were similar among CHEW and nurse/midwife clients—0.5 percent and 0.4 percent, adjusted odds ratio (aOR) 0.92 (95 percent CI 0.38–2.23)—but noninferiority could not be established. At follow‐up 6.6 percent of CHEW clients and 2.1 percent of nurse/midwife clients experienced AEs. There was strong evidence of effect modification by State. In the final adjusted model, odds of AEs for CHEW clients in Kaduna was 3.34 (95 percent CI 1.53–7.33) compared to nurse/midwife clients, and 0.72 (95 percent CI 0.19–2.72]) in Ondo. Noninferiority could not be established in either State. Implant expulsions were higher among CHEW clients (142/2987) compared to nurse/midwives (40/3517). Results show the feasibility of training CHEWs to deliver implants in remote rural settings but attention must be given to provider selection, training, supervision, and follow‐up to ensure safety and quality of provision.